2002
DOI: 10.1152/ajprenal.00265.2001
|View full text |Cite
|
Sign up to set email alerts
|

CytochromeP-450 4A isoform expression and 20-HETE synthesis in renal preglomerular arteries

Abstract: 20-Hydroxyeicosatetraenoic acid (20-HETE), a potent vasoconstrictor and mediator of the myogenic response, is a major arachidonic acid metabolite in the microvasculature of the rat kidney formed primarily by the cytochrome P-450 (CYP) 4A isoforms, CYP4A1, CYP4A2, and CYP4A3. We examined CYP4A isoform expression and 20-HETE synthesis in microdissected interlobar, arcuate, and interlobular arteries; mRNA for all CYP4A isoforms was identified by RT-PCR. Western blot analysis indicated that the levels of CYP4A2/4A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
75
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 31 publications
4
75
0
1
Order By: Relevance
“…Early studies in the SHR suggested that an increase in vascular-derived 20-HETE acts to enhance preglomerular vascular tone, which leads to resetting of the pressure-natriuretic response and the development of hypertension. 13,14 This hypothesis is consistent with the observations that acute treatment of SHR with ABT, an inhibitor of 20-HETE production, or antisense oligonucleotides directed against the Cyp4a1 isoform is able to decrease vascular reactivity and lower blood pressure. 15,16 However, the results of other studies indicating that the induction of the renal production of 20-HETE with fibrates reduces blood pressure in the SHR have suggested an opposing role for tubular derived 20-HETE in the regulation of blood pressure in this model.…”
Section: Discussionsupporting
confidence: 86%
“…Early studies in the SHR suggested that an increase in vascular-derived 20-HETE acts to enhance preglomerular vascular tone, which leads to resetting of the pressure-natriuretic response and the development of hypertension. 13,14 This hypothesis is consistent with the observations that acute treatment of SHR with ABT, an inhibitor of 20-HETE production, or antisense oligonucleotides directed against the Cyp4a1 isoform is able to decrease vascular reactivity and lower blood pressure. 15,16 However, the results of other studies indicating that the induction of the renal production of 20-HETE with fibrates reduces blood pressure in the SHR have suggested an opposing role for tubular derived 20-HETE in the regulation of blood pressure in this model.…”
Section: Discussionsupporting
confidence: 86%
“…6,7 CYP4A proteins are present in vascular tissues and show distinct distribution along the vascular tree. 8 Suppression and overexpression of CYP4A proteins in small arteries and arterioles decreases and increases, respectively, vascular reactivity and myogenic tone 7,9,10 ; these effects can be reversed by the addition of 20-HETE or inhibition of its synthesis.…”
mentioning
confidence: 99%
“…Four CYP4A isoforms (CYP4A1, CYP4A2, CYP4A3, and CYP4A8) are expressed in the kidney of rats, and these isoforms are able to catalyze the hydroxylation of fatty acids and produce 20-HETE. 14 Salt sensitivity is the causative agent for an important subgroup of humans with essential hypertension. 11 Considerable evidence suggests that endothelial dysfunction is linked to end-organ damage in human salt-sensitive hypertension.…”
mentioning
confidence: 99%